Comparative Study of Port Site Infection rate in Laparoscopic Cholecystectomy during Removal of Specimen with or without using Endobag in a Medical College Hospital (Central Medical College Journal, 2026)
Background: Port site infection (PSI) remains an important complication following laparoscopic cholecystectomy, particularly during gallbladder specimen retrieval. The role of endobag use in reducing infection, especially in cases with gallbladder perforation and bile spillage, is still debated. Objective: To compare the rate of port site infection during gallbladder specimen removal with and without the use of an endobag in laparoscopic cholecystectomy. Methods: This prospective randomized comparative study was conducted in the Department of Surgery at Kumudini Women’s Medical College from October 2024 to October 2025. A total of 56 patients undergoing elective laparoscopic cholecystectomy were included and divided into two groups: Group A (non-perforated gallbladder retrieval without endobag) and Group B (perforated gallbladder retrieval with endobag), each containing 28 patients. Statistical analysis was performed using SPSS version 26. Results: The mean age of patients was 41.4 ± 10.2 years. Female predominance was observed (80.4%). Port site infection occurred in 3.6% of Group A and 14.3% of Group B. Bile spillage was significantly higher in Group B (39.3%) compared to Group A (7.1%), and was significantly associated with port site infection (p=0.012). Mean hospital stay was longer in Group B. Conclusion: Port site infection is significantly associated with gallbladder perforation and bile spillage during specimen retrieval. Although endobag use is common in perforated cases, infection risk remains higher in these patients. Careful surgical technique to prevent perforation is crucial in reducing postoperative infection.Central Medical College Journal Vol 9 No 2 July 2025 Page: 70-75